Efficient thermochemical liquefaction of microalgae Haematococcus pluvialis for production of high quality biocrude with high selectivity over Fe/montmorillonite catalyst. (August 2021) - Hong, Weitu; Chen, Junhong; Ding, Qiuyu; Gao, Yuxing; Ye, Liyi; Yin, Yingwu; Tu, Song
Abstract: Thermochemical liquefaction (TCL) of microalgae Haematococcus pluvialis over diverse metal-supported montmorillonite catalysts at lower temperature was studied. This study aimed to investigate the liquefaction conditions for producing high quality biocrude from microalgae with high selectivity. Metal-supported montmorillonite catalysts, which are cheap, efficient and could be prepared conveniently, are firstly reported to produce biocrude from microalgae. Using Fe/montmorillonite as catalyst and methanol as solvent, the liquefaction of Haematococcus pluvialis could obtain a maximal biocrude yield of 68.9% and the highest selectivity of 99.4% at low temperature (200 °C). The methanol-ethanol co-solvents were also applied to liquefaction of microalgae. The co-solvents exhibited a good synergistic effect and helped for liquefaction of microalgae. Meanwhile, Fe/montmorillonite catalyst could promote cracking reactions of non-volatile tarry residue and change the composition of biocrude. Gas chromatography-mass spectrometry (GC-MS) analysis demonstrated that major compounds in biocrude were esters, and the contents of fatty acids and N -containing compounds in biocrude were decreased significantly by adding Fe/montmorillonite. Graphical abstract: Image 1 Highlights: Developing a novel Fe/montmorillonite catalyst for liquefaction of Haematococcus pluvialis with alcohols. Fe/montmorillonite was an effective catalyst to improve the yield and selectivity of biocrude. Adding Fe/montmorillonite catalyst in the liquefaction of Haematococcus pluvialis improved the quality of biocrude.